2011
DOI: 10.1007/s00213-011-2605-9
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate produces selective enhancement of declarative memory consolidation in healthy volunteers

Abstract: RationaleMethylphenidate inhibits the reuptake of dopamine and noradrenaline and is used to treat children with attention deficit hyperactivity disorder (ADHD). Besides reducing behavioral symptoms, it improves their cognitive function. There are also observations of methylphenidate-induced cognition enhancement in healthy adults, although studies in this area are relatively sparse. We assessed the possible memory-enhancing properties of methylphenidate.ObjectiveIn the current study, the possible enhancing eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 46 publications
2
58
1
Order By: Relevance
“…On the other hand, it may reasonably be expected that a cognition enhancer would also be able to improve cognition in such a population. This was demonstrated in two studies examining the effects of the cognitive enhancer methylphenidate in healthy young volunteers: methylphenidate was found to decrease response times and improve episodic memory in one study (Linssen et al 2014) and to improve declarative memory, attention, and response inhibition in another study (Linssen et al 2012). We did find some effects of caffeine, although it must be mentioned that absolute differences were relatively small.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, it may reasonably be expected that a cognition enhancer would also be able to improve cognition in such a population. This was demonstrated in two studies examining the effects of the cognitive enhancer methylphenidate in healthy young volunteers: methylphenidate was found to decrease response times and improve episodic memory in one study (Linssen et al 2014) and to improve declarative memory, attention, and response inhibition in another study (Linssen et al 2012). We did find some effects of caffeine, although it must be mentioned that absolute differences were relatively small.…”
Section: Discussionsupporting
confidence: 61%
“…12 Among those who used such substances, MPH was the drug of choice, accounting for 62% of the total. Evidence has suggested that MPH improves executive functions and memory in healthy individuals 13 ; some authors advocate its use, legalization and even the encouragement of such use. 12,14,15 However, the use of MPH for cognitive enhancement is controversial, because neither drug efficacy nor the benefit-risk balance provide sufficient evidence for this use.…”
Section: Introductionmentioning
confidence: 99%
“…Three were investigating single doses of d-amphetamine of which all three reported positive effects on delayed recall or recognition (Zeeuws et al 2010a, b;Zeeuws and Soetens 2007). Four were investigating single doses of methylphenidate of which two reported positive effects on delayed recall memory (Izquierdo et al 2008;Linssen et al 2012) and two found no difference (Hermens et al 2007;Kuypers and Ramaekers 2005). The studies that reported positive effects had in common that they were using considerably longer word lists (20, 30, 70 words) opposed to the studies not reporting positive effects (12 and 15 words) and were looking at late stage memory consolidation.…”
Section: Dopaminementioning
confidence: 98%